Cash transfers for sustainable rural livelihoods? Examining the long-term productive effects of the Child Support Grant in South Africa. (September 2020) - Hajdu, Flora; Granlund, Stefan; Neves, David; Hochfeld, Tessa; Amuakwa-Mensah, Franklin; Sandström, Emil
Highlights: Examines long-term 'productive' impacts of small cash transfers on rural livelihoods. Significant positive correlations found for productive assets, gardening and poultry. No significant correlation found for securing employment or engaging in petty trade. Cash transfers generate important productive effects, but not sustainable livelihoods. Structural and contextual constraints must be addressed together with cash transfers. Abstract: Cash transfers have received increased scholarly and policy attention, as a means of reducing poverty in the global South. While cash transfers are primarily intended to prevent impoverishment and deprivation, several studies suggest they can have 'productive' impacts, contributing to building sustainable livelihoods. However, pilot projects of unconditional cash transfers have often been too brief or too recent to determine how small, but regular, transfers can improve rural livelihoods over time. This paper explores potential long-term productive effects of cash transfers on rural household's livelihoods. This is done through revisiting, after 14 years, all (273) households in two South African villages included in an extensive livelihood and asset survey in 2002. That survey predated the phasing in of the Child Support Grant (CSG), targeted at impoverished children. When re-surveyed in 2016, some households had cumulatively received significant, while others little or no CSG income. Multivariate regression analysis shows how households that received more CGS income were more likely to invest in productive assets (e.g. small ploughs), and engage in poultry, staple crop and vegetable production. We also found a statistically significant correlation between CSG incomes and growing a larger variety of crops, in an environment generally marked by deagrarianization. However, correlations between receiving more CSG and employment or engagement in informal small-scale trade were not significant. We use data from interviews and observations to explain these processes further. Compared with the paucity of outcomes from other concurrent and costly development interventions in the focal villages, cash transfers have improved livelihoods and living conditions significantly. However, the structural and contextual factors that cause and reproduce poverty remain unaltered, limiting the effects of comparatively small cash transfers. While we show that the cash transfers generate productive livelihood-enhancing effects, they remain insufficient to lift most households out of poverty without further structural changes and developmental interventions.